(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This article shows the task of a teacher of the present time – methods of teaching students to study using new pedagogical technologies. Audience in mathematics the results of observations on the use of the proposed method of organizing independent work of students in classes.